Review of Chinese species of the Oxylipeurus-complex (Phthiraptera: Philopteridae), with descriptions of two new genera and five new species - Gustafsson, Daniel R.; Lei, Lujia; Chu, Xingzhi; Zou, Fasheng (Zootaxa, 2020)
Chewing lice of the Oxylipeurus-complex known from China are described and illustrated. The genera Megalipeurus Kéler, 1958 and Reticulipeurus Kéler, 1958 are considered valid, resurrected from synonymy and redescribed. Two new genera are described: Cataphractomimus new genus and Sinolipeurus new genus, which are proposed for species that do not fit into any previously described genus within the Oxylipeurus-complex. The following species are redescribed and illustrated: Reticulipeurus mesopelios (Nitzsch [in Giebel], 1866); Reticulipeurus robustus (Rudow, 1869); Reticulipeurus reevesi (Clay, 1938); Reticulipeurus baileyi (Clay, 1938); Reticulipeurus crossoptilon (Clay, 1938); Reticulipeurus ithaginis (Clay, 1938); Sinolipeurus tetraophasis (Clay, 1938) new combination. Several species previously placed in the genus Oxylipeurus are given new generic combinations. In addition, the following five new species are described and illustrated: Megalipeurus sinensis new species ex Arborophila gingica (Gmelin, 1789); Cataphractomimus mirapelta new species ex Lophophorus lhuysii Geoffroy Saint-Hilaire, 1866; Cataphractomimus impervius new species ex Lophophorus sclateri sclateri Jerdon, 1870; Cataphractomimus junae new species and Sinolipeurus sichuanensis new species ex Tragopan temminckii (J.E. Gray, 1831).